Penerapan Media Audiovisual untuk Meningkatkan Hasil Belajar Siswa Sekolah Dasar - Amalia, Zafirah Nur; Gumala , Yosi (Ruang Publikasi Ilmiah, 2025)
The purpose of this study is to see how much influence audiovisual media has on student learning outcomes in elementary schools. This study uses a literature review approach to achieve this goal, by analyzing various previous studies relevant to this topic. Researchers collected 30 articles from DOAJ, Sinta, Index Copernicus and Google Scholar journals by collecting, analyzing, and synthesizing the results of relevant previous studies to build a theoretical framework and empirical basis and then working on it through identification by reading, analyzing, categorizing, classifying and describing. With the results of the study proving that audiovisual media plays an important and effective role in achieving learning outcomes and contributes significantly, there are many benefits to using audiovisual learning media as an alternative to utilizing technological advances to help students be more motivated to learn because the material is presented in an interesting way. By creating fun learning media, students will feel more confident and motivated to achieve their maximum learning potential.